2023
DOI: 10.1177/00099228231191926
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Caregiver and Provider Food Insecurity Screening Preferences Within a Health System

Abstract: Food insecurity is a public health concern associated with poor health. Evidence guiding how to best implement screening for food insecurity across a pediatric health care system is lacking. We performed a single-center, multi-department, cross-sectional study of caregivers and health care providers in outpatient and inpatient settings to describe the beliefs, barriers, preferences, and preferred food insecurity screening location. Most providers and caregivers underestimated the pervasiveness of food insecuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Most participants agreed that discussing FI during their medical encounter could benefit their health, although those who were experiencing FI did report more discomfort with the process. 22 Cullen et al showed that compared to verbal screening, patients screened by tablets had higher reported rates of FI and greater satisfaction with the process. 8 A successful screening process would need to be sensitive to potential feelings of shame among patients who are food insecure, ensuring patient privacy is protected at all times.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants agreed that discussing FI during their medical encounter could benefit their health, although those who were experiencing FI did report more discomfort with the process. 22 Cullen et al showed that compared to verbal screening, patients screened by tablets had higher reported rates of FI and greater satisfaction with the process. 8 A successful screening process would need to be sensitive to potential feelings of shame among patients who are food insecure, ensuring patient privacy is protected at all times.…”
Section: Discussionmentioning
confidence: 99%